TOWARDS USABILITY INTEGRATION INTO E-LEARNING DESIGN - Jirgensons, Merija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
While e-learning use has sharply increased, the drop-out rate is high. This paper addresses some of the aspects that cause users to reject e-learning and not finish. It focuses on the concept of “usability”, especially pedagogical usability that is currently central to usability design. While the term is nebulous, it is identified by attributes such as learnability, efficiency and (subjective) satisfaction. Attributes can be measured and designers add new ones as the need arises. Satisfaction has become the focus of pedagogical usability experts who claim the term includes motivational and emotive factors and may be measured by psychometric testing. Currently, efforts are underway to integrate pedagogical usability into e-learning design and create attractive, flexible features that are easy to handle and available on demand. Efforts are also underway to design mobile learning that incorporates usability principles. Usability improvements have been incremental because the e-learning process is not clear to designers, but it is expected that awareness and innovations will correct this problem in the future.